2017
DOI: 10.2147/ott.s140221
|View full text |Cite
|
Sign up to set email alerts
|

Distinct prognostic values of alcohol dehydrogenase mRNA expression in pancreatic adenocarcinoma

Abstract: BackgroundAlcohol dehydrogenase (ADH) isoenzymes have been reported as a potential diagnostic marker for pancreatic cancer, but their prognostic value in pancreatic cancer remains unclear. The aim of this investigation was to identify the prognostic value of ADH genes in human patients with pancreatic adenocarcinoma (PAAD).Materials and methodsAn RNA sequencing dataset and corresponding survival profiles of PAAD were obtained from The Cancer Genome Atlas. Survival analysis and gene set enrichment analysis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 61 publications
10
19
0
Order By: Relevance
“…Whereas, the expression of ADH5 were signi cantly upregulated in HCC tissues compared to normal liver tissues (Fig. 1E), consistent with what is already known in NSCLC, gastric cancer, and pancreatic adenocarcinoma [19,20,29]. In addition, previous studies have reported the positive correlation of ADHs with each other in numerous cancers [19,20]; here, our results also con rmed that in HCC (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas, the expression of ADH5 were signi cantly upregulated in HCC tissues compared to normal liver tissues (Fig. 1E), consistent with what is already known in NSCLC, gastric cancer, and pancreatic adenocarcinoma [19,20,29]. In addition, previous studies have reported the positive correlation of ADHs with each other in numerous cancers [19,20]; here, our results also con rmed that in HCC (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Primarily, our results revealed that the expression levels of ADH1A-ADH4, and ADH6 were signi cantly decreased in HCC tissues compared to normal liver tissues (Fig. 1), which were similar to their expression in non-small cell lung cancer (NSCLC) and pancreatic adenocarcinoma [19,29]. Therefore, we speculate that ADH1A-ADH4, and ADH6 may serve as tumor suppressors in HCC.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, high expression levels of the ADH1A and ADH6 genes have a beneficial effect on the course of adenocarcinoma of the pancreas. Conversely, an increased activity of ADH5/FDH, oxidizing formaldehyde, has been noted by oncologists to be an unfavorable factor in the course of the disease . The same pattern was found in the study of patients with gastric cancer …”
Section: Genes Involved In the Metabolism Of Alcohols And Aldehydes supporting
confidence: 58%
“…Moreover, the authors suggested that the ADH1B, ADH1C, and ADH4 genes can function as tumor suppressors, while ADH5/FDH and ADH7 probably play an oncogenic role in the carcinogenesis of NSCLC. The analysis of isoenzymes of ADH is also of diagnostic value in brain cancer, stomach cancer, and adenocarcinoma of the pancreatic gland . Moreover, high expression levels of the ADH1A and ADH6 genes have a beneficial effect on the course of adenocarcinoma of the pancreas.…”
Section: Genes Involved In the Metabolism Of Alcohols And Aldehydes mentioning
confidence: 99%
“…MAK3/NAA30 , a component of the NatC complex ( Fig 8A ), induces p53-dependent apoptosis when knocked down in cancer cell lines [184]. The HLD-specific deletion enhancer, SFA1 , has seven human homologs, of which three ( ADH4, ADH1A , and ADH6 ) were UES in gCSI data ( Additional File 1, Figure S7) ‥ High expression of ADH1A or ADH6 was predictive of improved prognosis for pancreatic adenocarcinoma [185] and high expression of ADH1A or ADH4 had improved prognosis for non-small cell lung cancer [186]. The ERG13 homolog, GCS1 , has been suggested as a synthetic lethal target for BRAF V600E -positive human cancers [187], and HMGCS2 plays a role in invasion and metastasis in colorectal and oral cancer [188].…”
Section: Resultsmentioning
confidence: 99%